A Code-Based ISE to Protect Boolean Masking in Software - Qi Tian; Hao Cheng; Chun Guo; Daniel Page; Meiqin Wang; Weija Wang (Transactions on Cryptographic Hardware and Embedded Systems, 2025)
Side-Channel Attacks (SCAs) pose a significant threat to data security in embedded environments. To counteract the power-based SCAs, masking is a widely used defense technique, that introduces randomness to obscure the sidechannel information generated during the processing of secret data. However, in practice, some challenges exist when implementing masking schemes. For example, in the implementation of Boolean masking, they may refer to low noise level and implementation flaws. To address the said implementation challenges, we present an effective and efficient solution that incorporates the code-based masking technique: We mask the shares of Boolean masking with code-based masking and then use a selfdesigned Instruction Set Extension (ISE) to perform efficient private computations within this masked domain. Based on a 32-bit RISC-V Ibex core, we develop a prototype implementation of our ISE, whereby it mainly wraps the ALU with three code-based encoders/decoders and integrates a leakage-resilient pseudo-random generator (PRG). Compared to the base core (vanilla Ibex), the hardware overhead of the ISE implementation is only 8%. The security evaluation based on formal verification and practical evaluation demonstrates that our ISE can provide a more robust practical security guarantee. Furthermore, our approach significantly reduces the signal-to-noise ratio (SNR) of each share, decreasing it to just 2% of the original SNR on the base core.